Bioavailability and bioequivalence comparison of brivaracetam 10, 50, 75, and 100 mg tablets and 100 mg intravenous bolus. (26th June 2016) - Stockis, Armel; Hartstra, Jan; Mollet, Muriel; Hadi, Salah
Summary: Objective: To determine the bioequivalence of brivaracetam oral tablet formulations (10, 75, and 100 mg) versus 50 mg oral tablet and to compare the bioavailability of brivaracetam 100 mg intravenous (i.v.) bolus versus 50 and 100 mg tablets, in healthy participants. Methods: Phase 1, randomized, open‐label, five‐period crossover study. Participants received five single doses of brivaracetam: 10, 50 (reference), 75, and 100 mg oral tablets; 100 mg, i.v., bolus injection. Pharmacokinetic parameters (maximum plasma concentration [Cmax ], area under the plasma concentration‐time curve from time zero to the time of last quantifiable concentration [AUCt ], area under the plasma concentration‐time curve extrapolated to infinity [AUCinf ]) were compared using analysis of variance (ANOVA) following dose normalization and logarithmic transformation. Bioavailability comparisons were based on the 90% confidence intervals (CIs) around the geometric least squares mean ratios (test: reference). Results: Twenty‐five participants were randomized. The 90% CIs around Cmax, AUCt, and AUCinf ratios for brivaracetam 10, 75, and 100 mg tablets versus 50 mg tablet were entirely contained within the bioequivalence limits (0.8000–1.2500). For brivaracetam 100 mg, i.v., bolus, bioequivalence versus 50 and 100 mg tablets was met for AUCt and AUCinf, but Cmax was partly outside the limits (90% CI: 1.1867–1.3863 and 1.1222–1.3136, respectively). Significance: Brivaracetam 10, 75, and 100 mg tablets were bioequivalent to the 50 mg tablet. Brivaracetam 100 mg, i.v., bolus had bioavailability similar to that of 50 and 100 mg tablets.